2013
DOI: 10.4321/s1578-84232013000200009
|View full text |Cite
|
Sign up to set email alerts
|

Consideraciones en el entrenamiento de habilidades psicológicas en esgrima

Abstract: Resumen: El objetivo de estudio fue conocer si existen diferencias en las habilidades psicológicas del esgrimista de competición en función de su nivel deportivo, edad y género. Fueron evaluados 90 esgrimistas (42 mujeres y 48 hombres; 20 élite y 70 no-élite; edad: M= 21.20, dt= 7.01) sin entrenamiento psicológico previo. Se aplicó la Prueba para Evaluar Rasgos Psicológicos en Deportistas Versión Revisada (PAR P1-R; Serrato, 2006). Un MANOVA mostró diferencias significativas por nivel deportivo (Lambda de Wilk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 11 publications
0
2
0
4
Order By: Relevance
“…Nuñez et al [ 41 ]) using a systematic review, this relationship is found to be very weak and nuanced by the role of different mediating factors, such as previous sports experience or the competitive level (e.g. Rascado, et al [ 42 ]; Reche, Cepero & Rojas [ 43 ]), despite the belief—even among professional and academic circles—that there is a strong relationship between negative variables and poor performance, and vice versa, with respect to the positive variables.…”
Section: Discussionmentioning
confidence: 99%
“…Nuñez et al [ 41 ]) using a systematic review, this relationship is found to be very weak and nuanced by the role of different mediating factors, such as previous sports experience or the competitive level (e.g. Rascado, et al [ 42 ]; Reche, Cepero & Rojas [ 43 ]), despite the belief—even among professional and academic circles—that there is a strong relationship between negative variables and poor performance, and vice versa, with respect to the positive variables.…”
Section: Discussionmentioning
confidence: 99%
“…El Par P1-R el cual es un inventario de habilidades psicológicas que permite evaluar el perfil psicológico de los tenistas a partir de las siguientes habilidades: Autoconfianza, motivación, concentración, sensibilidad emocional, imaginación, actitud positiva y reto competitivo; este test ha sido utilizado ampliamente en los estudios de Serrato, 2006;García, Cepero & Rojas (2010) en el campo del deporte.…”
Section: Instrumentos Utilizadosunclassified
“…En consecuencia, la participación en el fútbol de iniciación deportiva actual supone inmiscuirse en un espacio formativo que demanda una resolución de conducta compleja, discordante con sus posibilidades de comprensión neuropsicológicas (García, Rodríguez, & Garzón, 2011; Tirapu & Luna, 2007); esto conlleva aprendizajes y demandas de gestión emocional a edades más tempranas a lo que formalmente se propone. El currículo del sistema educativo español no prevé el desarrollo de contenidos de deportes de cooperación-oposición hasta los 10 años (Muñoz, 2014), mientras que la competencia emocional prevista hasta los seis años se reduce a conciencia — interpretar la realidad — autocontrol — naturalidad en comportamiento — desarrollo incipiente de autoconcepto y autoestima e interacciones sociales positivas (Sánchez, 2010).…”
Section: La Gestión Emocional Del Niño En La Competición Escolar: El ...unclassified
“…In consequence, participation in introductory football today means getting involved in a formative space that requires the resolution of complex behaviour, which is discordant with the participants’ potential neuropsychological understanding (García, Rodríguez, & Garzón, 2011; Tirapu & Luna, 2007); this leads to lessons and demands for emotional management at earlier ages than needed formally. The curriculum in the Spanish educational system does not include the development of cooperative-oppositional sports contents until the age of 10 (Muñoz, 2014), while the emotional competences covered by the age of six are limited to awareness (interpreting reality), self-control (naturalness in behaviour), incipient development of self-concept and self-esteem and positive social interactions (Sánchez, 2010).…”
mentioning
confidence: 99%